Shanduka Black Umbrellas : giving impetus to Black enterprises - Mthanti, Thanti; Townsend, Stephanie (London : Wits Business School, 2016)
In September 2016, Seapei Mafoyane, chief executive officer (CEO) of Shanduka Black Umbrellas (SBU), a business incubator targeting emerging black-owned enterprises, was busy writing her annual review for inclusion in SBU's 2016 annual report. She believed that SBU had an essential role to play in ensuring the success of black entrepreneurs in South Africa, among whom the failure rate was notoriously high.While SBU's incubator programme was helping many businesses that might otherwise have failed, she wondered whether the organisation could do anything to improve its success rate. This would not only benefit the black entrepreneurs themselves, but the South African economy as a whole.Was SBU on the right track in the methods it was using to assist black entrepreneurs, or should it change its approach in any way?
Originally published in Mthanti, T., & Townsend, S. (2016). Shanduka Black Umbrellas: Giving impetus to Black enterprises. WBS-2016-13. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mafoyane, Seapei; Shanduka Black Umbrellas; Businesspeople, Black -- South Africa; New business enterprises -- South Africa -- Management